Program Kelas Mengenal Difabel (KMD) Upaya Komunitas GPAD dalam Mewujudkan Masyarakat Inklusi di Pekalongan - Kholis, Ahmad Nur KHolis; Arizal Mutahir; Muslihudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main problem faced is the low level of understanding and social inclusion of people with disabilities in Pekalongan. The Recognizing Disability Class (KMD) program carried out by the GPAD Pekalongan Community aims to overcome this problem through inclusive and interactive education. This program seeks to change negative stigma, develop empathy and deep understanding, and increase active community participation in supporting people with disabilities. The research method is a qualitative method. The data collection method is through interviews, observation and documentation. The results of the analysis show that KMD increases public awareness and understanding. KMD uses an inclusive approach involving interactive learning methods and relevant contextual materials.